2015
DOI: 10.1186/s12991-015-0069-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for depression in women with multiple sclerosis: a study from Iran

Abstract: BackgroundMultiple sclerosis is increasingly becoming a major health problem among women worldwide. The aim of the present study was to estimate prevalence of depression in women with multiple sclerosis and also to identify risk factors contributing to its development.MethodsThis was a cross-sectional study of depression in a sample of 226 women with multiple sclerosis. The sample was recruited from an outpatient clinic in Tehran, Iran. Depression was assessed using the Beck Depression Inventory-II (BDI-II). U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Iranian study (2004) showed that the prevalence of depression in physically disabled veterans was (71%) [5], while recent Iranian study (2015) found 91 of 226 (40.2%) had moderate to severe depression [32]. Estimates of the prevalence of depression are affected by the nature of the measures used, how depression is defined, aging characteristics of the samples studied, and when symptoms are assessed post-injury.…”
Section: Discussionmentioning
confidence: 99%
“…Iranian study (2004) showed that the prevalence of depression in physically disabled veterans was (71%) [5], while recent Iranian study (2015) found 91 of 226 (40.2%) had moderate to severe depression [32]. Estimates of the prevalence of depression are affected by the nature of the measures used, how depression is defined, aging characteristics of the samples studied, and when symptoms are assessed post-injury.…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy between the sexes was not seen in a study investigating depression 20 and is not known for cognition impairment. 18 In a small study, depression correlated with disability and negatively with employment status 21 and may help to interpret our data. Interestingly, whereas females were more often affected by neuropsychological symptoms, males were more frequently affected by walking impairment, spasticity and ataxia.…”
Section: Discussionmentioning
confidence: 80%
“…It has influences on the general health and quality of life in patients with MS with a significant increase in the risk of suicide [ 7 ]. It generally starts after the diagnosis of MS and it is often associated with disabilities [ 8 ]. Some studies conflict that high scores of disability are related to the severity of depression [ 8 - 9 ], as Marrie et al reported that MS patients with high disabilities were having a six times risk for developing depression as compared to low disability [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…It generally starts after the diagnosis of MS and it is often associated with disabilities [ 8 ]. Some studies conflict that high scores of disability are related to the severity of depression [ 8 - 9 ], as Marrie et al reported that MS patients with high disabilities were having a six times risk for developing depression as compared to low disability [ 10 ]. Moreover, another study demonstrated that smoking, exercise, social support, omega 3, and vitamin D supplementation were the preferred medication, and widely differentiated modifiable lifestyle factors may reduce the depression risk as a preventative [ 11 ].…”
Section: Introductionmentioning
confidence: 99%